STUDY OF BABY DIAPERS WASTE MANAGEMENT IN SOUTH JAKARTA CITY - Tiara, Angelique
The birth rate in the Administrative City of South Jakarta was recorded to have increased by 1496 people (21.3%) in March 2020. This could affect the need for baby diapers to increase. Based on the results of the online questionnaire with a total of 400 respondents, there are two types of baby diapers used, namely disposable diapers at 99.25% and cloth diapers at 0.75%. The average frequency of baby diaper waste disposal is 4 diapers/day/respondent. The generation of baby diaper waste in Administrative City of South Jakarta is estimated at 177.35 tons/day. The projected generation of baby diaper waste for the next 10 years is estimated at 177.30 tons/day. The management of baby diaper waste on a household scale that can be done is sorting and washing baby diapers. In an effort to reduce the waste of baby diapers in the landfill and the negative impact on the environment and health, it is necessary to develop sustainable baby waste. Community participation is needed in the management of baby diapers so that a circular economy can be realized. Respondents who participated by 87% and did not participate by 13%. Meanwhile, respondents who are willing to pay are 80.5% and those who are not willing to pay are 19.5%. The average value of WTP for the management of baby diapers waste in Administrative City of South Jakarta is Rp 40,758.00 for respondents who are willing to pay. The baby diaper waste management system consists of sorting, collecting, transporting, processing, and final processing.